The Vile Village - Snicket, Lemony; Illustrated by Helquist, Brett (London Egmont, 2010)
Why would anyone want to open a book containing such unpleasant matters as migrating crows, an angry mob, a newspaper headline, the arrest of innocent people, the Deluxe cell, and some very strange hats.
Include Illustrations
Keywords: Humorous stories, English -- Baudelaire, Violet (Fictitious character)